Controversial Issues of Enforcement of Anti-Corruption Legislation - Tuchak, Mykola (Theory and Practice of Public Administration, 2022)
Nowadays, the anti-corruption legislation study is significant for establishing such wording in the definitions that will be equally perceived by the subjects of responsibility and subjects of prevention and counteraction to corruption and will be effectively used in the mechanism of corruption prevention and counteraction. This modernization will allow for an effective anti-corruption policy in Ukraine. The object of the study is social relations arising in the process of combating corruption in Ukraine. The subject of the study is the organizational and legal regulation of prevention and counteraction corruption in the context of the modern anti-corruption strategy. The article aims to identify the disadvantages of law enforcement, contradictions, and gaps in the current anti-corruption legislation and to outline the ways to eliminate them. When analyzing the current anti-corruption legislation, it is impossible not to focus on such an aspect as the definition of family members under Article 1 and the declarant family members in the note of Article 46, and information about the object of declaration that was in the possession or use of the declarant family members in the second part of Article 46 of the Law of Ukraine “On Prevention of Corruption”. These definitions must be consistent for their uniform perception and implementation in preventing and counteracting corruption. Particular attention should be paid to the practicality of filing a declaration for the previous year by persons who have ceased activities related to the performance of state or local government functions or other activities specified in subparagraphs “a”, “c” and “d” of paragraph 2 of the first part of Article 3 of the Law mentioned above. It also substantiates the need to include the State Bureau of Investigation in the list of specially authorized subjects combating corruption.